Clinical spectrum of pediatric dermatoses in patients attending a tertiary care center in central Nepal - Paudel, Sangeeta; Uprety, Shraddha; Thapa, Pratichya (Journal of Chitwan Medical College, 2021)
Background: Skin diseases are common health problem in children all over the world. However, there is scarcity of epidemiological studies on pediatric dermatoses in Nepal. This study was done to identify the pattern and age variations of pediatric dermatoses in a tertiary care centre in central Nepal. Methods: All children 18 years and below with skin disease attending dermatology OPD between the period of June 15, 2019 to December 15, 2019 were included in the study. SPSS 20 was used for statistical analysis with which descriptive statistics was done. Results: A total of 2789 patients (60.1% male and 39.9% female) with 2895 diagnoses were recorded during this period. The most common dermatoses were infections and infestations (62.8%) followed by eczema (12.1%), acne (7.5%) and urticaria (4.8%). Pigmentary disorder constituted 2.6%. Insect bite reaction was seen in 2.6%, miliaria 2 %, papulosquamous disorders 1.5% followed by disorders of hairs and nails 0.9%. Conclusions: This study revealed the most prevalent skin diseases in children in specialized dermatology clinic in a developing country such as Nepal. Fungal infection was commonest disease in adolescent and school age children whereas bacterial infection was commonest in infants, toddler and preschool children. Acne was predominantly seen in adolescent.